An Analysis of Potential Incompatibility Between the Acts Amendment (Evidence of Children and Others) Act 1992 and Defendants' Rights - Pearson, V. F. (1996)
The need to balance the needs and rights of all parties is a central consideration in legal procedure. This is no simple task, however, when the interests of the defendant are often in direct contrast to those of the witness. Much of the contention arises from the ambiguity associated with the nature of both victims' and defendants' rights and the lack of clear guidelines for the resolution of conflict where such competing interests are involved. Because Australia has no document precisely delineating the nature and content of individual rights, the result is a reliance on an ill-defined combination of common law practice, conceptions of both natural rights and utilitarianism, international human rights agreements and legislative stipulations. In recent times, attention has been focused on the perceived inadequacies of legislation pertaining to the child witness in a criminal trial. There is considerable contemporary e:idence to suggest that the traditional justifications given to regulate the reception of children's evidence in courts of law were based on unsubstantiated notions of the inherent unreliability of children. The need to introduce legislative reform pertaining to the evidence of children was first articulated by the Child Sexual Abuse Task Force which finalised its report to the Western Australian government in 1987. In Aprill991, the Law Reform Commission of Western Australia published their Report on Evidence of Children and Other Vulnerable Witnesses, having been asked to review the law and practice governing the giving of such evidence in legal proceedings. Their recommendations formed the basis for the Acts Amendment (Evidence of Children und Others) Act 1992. Although there is widespread support for the introduction of measures to address the needs of the child witness, there does not appear to have been sufficient rigorous evaluation of the corresponding effect on defendants' rights, particularly the right to a fair trial. This right, although not protected or defined by statute, is recognised both in Australia's common law heritage and through our ratification of major international human rights agreements. Although there is a general acceptance that the right to a fair trial largely overrides other individual claims to rights within the trial setting, an important consideration is the inherent vulnerability of common law rights to abrogation or removal by statutory law. Similarly, international human rights agreements are not, of themselves, always adequately enforceable, and require the enactment of supportive domestic legislation to ensure that their provisions are upheld. This has not occurred in Australia to any great extent. The primacy of the right to a fair trial is not supported by the Acts Amendment (Evidence of Children and Others Act) 1992. Whilst some of the provisions of this Act, such as the amendments relating to competence and corroboration of evidence, have brought children onto equal footing with other (adult) witnesses, other provisions have encroached on the defendant's right to a fair trial. Of particular concern are the subtle erosion of the presumption of innocence, the effects on the ability of the defence to cross-examine witnesses effectively, and the widespread inequality which the defendant now suffers in contrast to other defendants whose alleged offences do not come under the auspices of the Act: Although in drafting the legislation some care was taken to address these concerns, there still exists a degree of incompatibility between the Acts Amendment (Evidence of Children and Others) Act 1992 and defendants' rights. Safeguards for the protection of defendants' rights contained in the Act are, at times, insufficient. The precise extent to which the provisions of the Acts Amendment (Evidence of Children and Others) Act 1992 encroach on the conception of trial fairness is difficult to ascertain, thus the current research has highlighted only those provisions of the Act which are potentially incompatible with defendants' rights. Future research must stringently investigate the actual (not perceived) impact of these provisions on all parties to the proceedings, including the defendant the child, defence and prosecution lawyers, judicial officers and jurors. Subsequent to this investigation, a re-evaluation of the legitimacy of the legislation may be required